Fluorescent analogues of BeKm-1 with high and specific activity against the hERG channel. (April 2019) - Vasseur, Lucie; Chavanieu, Alain; Combemale, Stéphanie; Caumes, Cécile; Béroud, Rémy; De Waard, Michel; Ducrot, Pierre; Boutin, Jean A.; Ferry, Gilles; Cens, Thierry
Abstract: Peptidic toxins that target specifically mammalian channels and receptors can be found in the venom of animals. These toxins are rarely used directly as tools for biochemical experiments, and need to be modified via the attachment of chemical groups (e.g., radioactive or fluorescent moieties). Ideally, such modifications should maintain the toxin specificity and affinity for its target. With the goal of obtaining fluorescent derivatives of BeKm-1, a toxin from the scorpion species Buthus eupeus that selectively inhibits the voltage-gated potassium ion channel hERG, we produced four active analogues using a model of BeKm-1 docking to the outer mouth of the channel. In these BeKm-1 analogues, the natural peptide was linked to the fluorescent cyanine 5 (Cy5) probe via four different linkers at Arg 1 or Arg/Lys 27 . All analogues retained their specificity towards the hERG channel in electrophysiological experiments but displayed a lesser affinity. These results validate our strategy for designing toxin analogues and demonstrate that different chemical groups can be attached to different residues of BeKm-1. Highlights: Recent structural data on the hERG ion channel allow modeling BeKm-1 docking to the outer mouth of the channel. The docking model identified solvent-exposed residues in BeKm-1 sequence for the attachment of chemical groups. Four BeKm-1 analogues were produced by labeling with a fluorescent dye the end of four different linkers. Electrophysiological recordings demonstrated that BeKm-1 analogues retain the toxin affinity and specificity towards hERG.